Catalytic meerwein-ponndorf-verley reductions over mesoporous silica supports: rational design of hydrophobic mesoporous silica for enhanced stability of aluminum doped mesoporous catalysts - Shylesh, S.; Kapoor, Mahendra P.; Juneja, Lekh R.; Samuel, Prinson R.; Srilakshmi, Ch; Singh, A. R. (Journal of Molecular Catalysis A-Chemical, 2009)
A series of aluminum isopropoxide-grafted mesoporous organosilica having ethane (-CH(2)-CH(2)-) and ethene (-CH=CH-) groups in the frame wall positions (ethane-silica, ethene-silica) as well as mesoporous silicas (MCM-41, MCM-48. SBA-15) through siloxide linkages were fabricated. The samples were used as catalysts in the Meerwein-Ponndorf-Verley reduction of ketones and aldehydes of different nature and size using secondary alcohols as the hydrogen transfer agents. Aluminum isopropoxide supported mesoporous silica samples show higher catalytic conversion and among them, the one-dimensionally channel oriented Si-MCM-41 supported aluminum isopropoxide shows better results than the three-dimensional Si-MCM-48 and the large pore Si-SBA-15. Compared to aluminum isopropoxide-grafted mesoporous silica samples, aluminum alkoxide-grafted organosilica samples shows better catalytic activity even in the presence of 10% of water and the better stability is attributed to the presence of integrated hydrophobic organic groups in the frame wall positions. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Aluminum isopropoxide; Mesoporous silica; Organosilica; reduction

Tin incorporated periodic mesoporous organosilicas (Sn-PMOs): synthesis, characterization, and catalytic activity in the epoxidation reaction of olefins - Sisodiya, Sheetal; Shylesh, S.; Singh, A. P. (Catalysis Communications, 2011)
Tin incorporated mesoporous organosilicas (Sn-PMO) having uniform hexagonal arrangements were prepared using alkyl trimethylammonium bromide surfactants under basic reaction conditions. Characterization techniques revealed that the structural ordering, morphology, and the percentage of tin incorporation depend critically on the hydrophobic chain length of surfactants. The Sn-PMO samples are thermally stable up to 500 degrees C under air atmosphere and were hydrothermally stable up to 100 h in boiling water. The organotinsilicates showed excellent catalytic activity and reusability in the epoxidation of norbornene and ciscyclooctene than an Sn-MCM-41 due to organic groups in the frame wall positions and the better accessibility of reactants to the active sites. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: epoxidation; Hydrothermal stability; Mesoporous; Organosilica; Sn-MCM-41; Sn-PMO